UNMC-VIER AutoVision database - Lim, Hann; Le Ngo, A.; Seng, K.; Ang, L. (2010)
Designing a driver assistance system has become a trend in the automotive technology to improve the security and efficiency of driving. However, there is no standard on-road database to verify the performance and effectiveness of algorithms. In this paper, an automotive vision database is created to assist researchers analyzing their designed algorithm in a more convincing way. The UNMC-VIER AutoVision database composes of a series of single view videos embodying the information of traffic signs, vehicles and single/multiple lanes. In addition, multi-views videos, with the aid of three cameras are included in the database providing more visual information in the panoramic view of traffic scene for analysis. The standard setup and calibration of the database is discussed in the paper. Some applications are discussed along with the use of the database. © 2010 IEEE.